An institutional approach to English language proficiency. Issue 2 (3rd March 2016) - Murray, Neil; Hicks, Margaret
Abstract : As the university student body becomes ever more diverse, the place and nature of English language provision is coming under unprecedented scrutiny and is the object of greater regulation. Today, more than ever before, institutions of higher education are being called to account for the way in which they support this diverse population in respect of their English language provision. Increasingly, auditing bodies are expecting universities to demonstrate a commitment to supporting students adequately in this area and to be able to articulate a systematic process for doing so, along with a sound rationale and conceptual framework. This has put pressure on English-medium universities everywhere to review their English language provision and to develop creative and theoretically-informed solutions to what is perceived by many in the sector as a complex and very pressing issue, particularly given its financial ramifications and its importance in terms of the student experience. This article describes one such initiative at the University of South Australia, outlining both its conceptualisation and issues around its implementation.